Uwarunkowania środowiskowe związku przedślubnego i małżeństwa a opiniowanie w sprawach o stwierdzenie nieważności małżeństwa przed Sądem Biskupim - Cynkier, Przemysław (Ius Matrimoniale, 2014)
Aim of the work: Analysis of the premarital relationship with consideration of individual factors of the prospective spouses, their level of social acceptance and their influence on the image and duration of the engagement period and marriage. Evaluation of the relation between social situation of the spouses and the breakdown of marriage. Material and method: Material included 68 cases of marriage annulment, which were proceeded by the Bishop Court in years 2007-2012. Complete court records and psychiatric-forensic examinations of complainants and defendants were analyzed. Information was coded in specially developed questionnaire, through which in systematical way the data was collected, classified, the frequency of occurrence of chosen factors was cataloged and essential correlations between them were examined by means of statistical analysis. Conclusions: The course of engagement period and decision about betrothal did not have connection with the examined environmental factors. Duration of the marriage did not have any connection with chosen material-domestic and environmental factors. Majority of couples did not dispose of own accommodation what did not result from the material situation. The younger men and women were while contracting a marriage the longer was its duration. Among the analyzed group of marriages there is no data to recognize the environmental factors, which are commonly considered to be attributable to the occurrence of mental disorders. Etiology of the disorders should be researched by expert witnesses in other spheres.